Transformation of Snow White to Ugly Duckling: Neurobehavioral Impact of Childhood Craniopharyngioma - Suravi Patra; Ashok K. Mahapatra (Indian Journal of Neurosurgery)
Abstract Neurobehavioral problems are seen in children with craniopharyngiomas both before and after treatment, which cause significant morbidity. Behavioral problems include aggressive behavior, hyperphagia, impaired school performance, and poor social behavior. These children have impairment in psychosocial functioning and have a poor quality of life. Family members face a lot of difficulty in managing these difficulties. These behavioral problems are difficult to manage even by the health-care givers as there are no evidence-based treatment protocols. Behavioral therapy has been documented to be of benefit in certain cases, and the authors here also demonstrate the usefulness of behavior therapy in managing the behavioral problems of a child who had a successful gross total excision of craniopharyngioma with an otherwise uneventful postoperative course.